2016
DOI: 10.1515/esp-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

Modeling early stage bone regeneration with biomimetic electrospun fibrinogen nanofibers and adipose-derived mesenchymal stem cells

Abstract: Abstract:The key events of the earliest stages of bone regeneration have been described in vivo although not yet modeled in an in vitro environment, where mechanistic cell-matrix-growth factor interactions can be more effectively studied. Here, we explore an early-stage bone regeneration model where the ability of electrospun fibrinogen (Fg) nanofibers to regulate osteoblastogenesis between distinct mesenchymal stem cells populations is assessed. Electrospun scaffolds of Fg, polydioxanone (PDO), and a Fg:PDO b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The results of mechanical strength test demonstrated that Young's modulus and tensile strength of PHBV nanofibrous membranes got decreased upon blending with fibrinogen. Although fibrinogen is a highly bioactive biomaterial but shows limited mechanical integrity compared to synthetic polymers . Incorporation of BR nanoparticles within the nanofibers resulted in a significant increase in Young's modulus and tensile strength of PHBV/FG/BR compared to PHBV/FG and PHBV membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of mechanical strength test demonstrated that Young's modulus and tensile strength of PHBV nanofibrous membranes got decreased upon blending with fibrinogen. Although fibrinogen is a highly bioactive biomaterial but shows limited mechanical integrity compared to synthetic polymers . Incorporation of BR nanoparticles within the nanofibers resulted in a significant increase in Young's modulus and tensile strength of PHBV/FG/BR compared to PHBV/FG and PHBV membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Although fibrinogen is a highly bioactive biomaterial but shows limited mechanical integrity compared to synthetic polymers. 16,[35][36][37] Incorporation of BR nanoparticles within the nanofibers resulted in a significant increase in Young's modulus and tensile strength of PHBV/FG/BR compared to PHBV/FG and PHBV membranes. In our previous study, it was demonstrated that the addition of BR nanoparticles into PHBV nanofibers up to 10% resulted in improved tensile strength and increased resistance to deformation of PHBV membranes because of the reinforcement effect of BR nanoparticles within the polymer matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Electrospinning is a well-established bottom-up fiber production method dating back to at least 1900 [1]. Electrospinning of polymers from liquid solutions is a technique that has been used widely in the generation of three-dimensional (3D) fibrous scaffolds for tissue engineering applications [2][3][4][5][6][7][8]. This technology allows formation of fibers with diameters ranging from tens of nanometers to several microns.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their unique features, the use of nanofibrous electrospun scaffolds in tissue engineering is expanding rapidly. Polycaprolactone/collagen/hydroxyapatite (PCL/col./HA) [60], fibrinogen/polydioxanone (Fg/PDO) [61], and polycaprolactone/polylactic acid (PCL/ PLA) [62] nanofibrous electrospun scaffolds have been shown to promote bone regeneration in vitro when seeded with human MSCs. In diabetic animal models, 3D poly(lactic acid-coglycolic acid) (PLGA) electrospun scaffolds have been used for chronic wound repair [63], while poly-L-lactide acid (PLLA) electrospun devices have been able to improve insulin Fig.…”
Section: Scaffoldsmentioning
confidence: 99%